2011
DOI: 10.5004/dwt.2011.2788
|View full text |Cite
|
Sign up to set email alerts
|

Role of EPS in membrane fouling of a submerged anaerobic-anoxic-oxic (A-A-O) membrane bioreactor for municipal wastewater treatment

Abstract: A B S T R AC TAn anaerobic-anoxic-oxic membrane bioreactor for real municipal wastewater treatment was operated under various conditions in order to investigate extracellular polymeric substances (EPS) properties and their role in membrane fouling. Test results showed that EPS, proteins in EPS (EPS p ) and carbohydrates in EPS (EPS c ) had correlations with membrane fouling. EPS p were found to have more signifi cant correlations with membrane fouling while EPS and EPS c had loose correlations with membrane fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The release of these compounds at these special intervals of time can be a result of bacterial metabolism or cell lysis which both of them report to the presence of an environmental stress or toxicity inside the bioreactor. However, the membrane fouling can be influenced by the presence of these substances which form a gel layer into the membrane surface ideal for further bacterial attachment, increasing the effect of membrane clogging potential [48,49]. In this study, it was noticed that the amount of polysaccharides and proteins released during the evoked periods were quite high with, respectively, 10 ± 0.1-20 ± 0.5 mg g MLVSS for proteins.…”
Section: Evolution Of Membrane Fouling and Smp Releasementioning
confidence: 86%
“…The release of these compounds at these special intervals of time can be a result of bacterial metabolism or cell lysis which both of them report to the presence of an environmental stress or toxicity inside the bioreactor. However, the membrane fouling can be influenced by the presence of these substances which form a gel layer into the membrane surface ideal for further bacterial attachment, increasing the effect of membrane clogging potential [48,49]. In this study, it was noticed that the amount of polysaccharides and proteins released during the evoked periods were quite high with, respectively, 10 ± 0.1-20 ± 0.5 mg g MLVSS for proteins.…”
Section: Evolution Of Membrane Fouling and Smp Releasementioning
confidence: 86%
“…[1][2][3]. However, membrane fouling leads to performance reduction, rapid pressure increase, or severe flux decline and frequent membrane cleaning, which directly result in the increase of maintaining and operating costs.…”
Section: Introductionmentioning
confidence: 98%
“…Many researchers focused on the relationship between EPS and membrane fouling in MBR, and diffident conclusions came out mainly attributed to the variations of feedwater characteristics and operating conditions. Some researchers (Cho et al 2005;Liu et al 2012;Wang et al 2009;Wang et al 2011) found that bEPS especially the loosely bound EPS (lbEPS) played a more significant role in membrane fouling, while others (Meng et al 2009) considered that the soluble EPS (or SMP) had greater impact on membrane fouling than bEPS. There are also some debates between proteins and polysaccharides in EPS for which one have more contribution on membrane fouling (Sweity et al 2011;Wang et al 2011).…”
Section: Eps Analysismentioning
confidence: 99%